دور برامج التكوين في تنمية روح المقاولاتية لدى طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية - زغادنية مريم ,بوثلجة رحيمة (My University, 2025)
الملخص : عنـوان الدراسـة: دور برامج التكوين في تنمية روح المقاولاتية لدى طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية -دراسة ميدانية مع طلبة شعبة الادارة والتسيير الرياضي-  أهـدف الدراسـة:  التعرف علىدور برامج التكوين في تطوير قدرة الطلبة على بناء رؤية مستقبلية واضحة وتحديد أهداف استراتيجية في مجال المقاولاتية.  ابراز كيفية مساعدة برامج التكوين على تنمية الشجاعة لدى الطلبة لمواجهة التحديات والمخاطر في ريادة الأعمال واتخاذ قرارات جريئة.  تحديد برامج التكوين في تعزيز مهارات الإقناع لدى الطلبة ليصبحوا قادرين على التأثير في الآخرين ودفعهم لدعم مشاريعهم الريادية.  التعرف على برامج التكوين ودورها في تعزيز حيوية ونشاط الطلبة، وتحفيزهم على المثابرة والعمل المستمر لتحقيق أهدافهم في مجال المقاولاتية.  تبيين برامج التكوين في تشجيع الطلبة على التطور الذاتي المستمر وتزويدهم بالمهارات اللازمة لمواكبة التغيرات في السوق والمجال التكنولوجي.  فرضـيات الدراسـة:  لبرامج التكوين دور في تطوير قدرة الطلبة على بناء رؤية مستقبلية واضحة وتحديد أهداف استراتيجية في مجال المقاولاتية.  تساعد برامج التكوين على تنمية الشجاعة لدى الطلبة لمواجهة التحديات والمخاطر في ريادة الأعمال واتخاذ قرارات جريئة.  لبرامج التكوين دور في تعزيز مهارات الإقناع لدى الطلبة ليصبحوا قادرين على التأثير في الآخرين ودفعهم لدعم مشاريعهم الريادية.  لبرامج التكوين دور في تعزيز حيوية ونشاط الطلبة، وتحفيزهم على المثابرة والعمل المستمر لتحقيق أهدافهم في مجال المقاولاتية.  لبرامج التكوين دور في تشجيع الطلبة على التطور الذاتي المستمر وتزويدهم بالمهارات اللازمة لمواكبة التغيرات في السوق والمجال التكنولوجي.  إجـراءات الدراسـة الميدانيـة:  العينـة: تم أخذ العينة 63 طالب شعبة الادارة والتسيير الرياضي.  المجـال الـزماني: امتد من 25نوفمبر 2024 إلى غاية 05ماي2025.  المجال المكاني: طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية جامعة سوق اهراس.  المنهـج المستخـــدم: تم إستخدام المنهج الوصفي بالنمط المسحي.  الأدوات المستعملـــة: إعتمدنا في دراستنا على إستمارةإستبيان.  النتائج المتـوصل إلـيها: لقد تم التوصل إلى النتائج التالية:  برامج التكوين تساهم بشكل فعّال في تعزيز التفكير المقاولاتي لدى الطلبة، مما يتيح لهم فهم المبادئ الأساسية لريادة الأعمال وتطبيقها في مجال لإدارة والتسيير الرياضي.  برامج التكوين تزوّد الطلبة بالمهارات العملية اللازمة لإدارة المشاريع الرياضية والريادة في هذا المجال، سواء من خلال التدريب العملي أو المحاكاة الواقعية.  اقتراحــات:  تعزيز التركيز على التدريب العملي في برامج التكوين، مما يمكن الطلبة من اكتساب الخبرات الحقيقية وتطبيق المبادئ التي تعلموها في بيئة العمل الفعلية.  تطوير برامج التكوين لتشمل التدريب على أحدث التقنيات والأدوات التي تساهم في تحسين الأداء الرياضي والإداري، بما في ذلك البرمجيات الرياضية والتقنيات الحديثة في تحليل البيانات وإدارة المشاريع. résumé : Titre :Le rôle des programmes de formation dans le développement de l'esprit entrepreneurial chez les étudiants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives – Étude de cas des étudiants de la filière Gestion et Administration Sportive. Objectifs de l’étude : • Identifier le rôle des programmes de formation dans la capacité des étudiants à construire une vision stratégique claire dans le domaine de l’entrepreneuriat. • Montrer comment la formation contribue à développer le courage des étudiants pour faire face aux défis et prendre des décisions audacieuses en entrepreneuriat. • Déterminer comment les programmes de formation renforcent les compétences de persuasion afin d’influencer et mobiliser les autres autour de leurs projets. • Étudier l’impact des formations sur la motivation, l’énergie et la persévérance des étudiants pour atteindre leurs objectifs entrepreneuriaux. • Mettre en évidence le rôle de la formation dans l'encouragement du développement personnel et l’acquisition des compétences nécessaires pour s’adapter aux changements du marché et aux avancées technologiques. Hypothèses de l’étude : • Les programmes de formation aident les étudiants à développer une vision stratégique claire dans le domaine entrepreneurial. • La formation joue un rôle dans le développement du courage nécessaire à la prise de risques et de décisions audacieuses. • Les programmes de formation renforcent les compétences de communication et de persuasion. • La formation stimule l’énergie, la motivation et la persévérance des étudiants. • Les programmes de formation encouragent le développement personnel et permettent l’adaptation aux évolutions technologiques et du marché. Méthodologie de l’étude : • Échantillon : 63 étudiants en Gestion et Administration Sportive. • Période : du 25 novembre 2024 au 5 mai 2025. • Lieu : Institut des Sciences et Techniques des Activités Physiques et Sportives, Université de Souk Ahras. • Méthode : Méthode descriptive – enquête par questionnaire. • Outil utilisé : Questionnaire distribué aux étudiants. Résultats obtenus : • Les programmes de formation contribuent efficacement à renforcer l’esprit entrepreneurial des étudiants, leur permettant de comprendre et d’appliquer les principes de l’entrepreneuriat dans le domaine sportif. • Ces formations offrent aux étudiants des compétences pratiques utiles à la gestion de projets sportifs, notamment à travers des activités de simulation ou des stages pratiques. Suggestions : • Renforcer la dimension pratique des formations pour permettre aux étudiants d’acquérir des expériences concrètes. • Développer les programmes en y intégrant les dernières technologies et outils utilisés dans la gestion et l’analyse sportive (logiciels spécialisés, gestion de projets, analyse de données, etc.). abstract : Study Title: The Role of Training Programs in Developing the Spirit of Entrepreneurship among Students of Science and Techniques of Physical and Sports Activities - A Field Study with Students of the Sports Administration and Management Division –  Objectives of the study:  Identify the role of training programs in developing students' ability to build a clear future vision and set strategic goals in the field of entrepreneurship. Highlight how training programs can help develop students' courage to face challenges and risks in entrepreneurship and make bold decisions.  Identify training programs to enhance students' persuasion skills to be able to influence others and push them to support their entrepreneurial projects.  Identify training programs and their role in enhancing the vitality and activity of students, and motivating them to persevere and work continuously to achieve their goals in the field of entrepreneurship.  Demonstrate training programs in encouraging students to continuous self-development and provide them with the necessary skills to keep pace with changes in the market and the technological field.  Studyhypotheses:  Training programs have a role in developing students' ability to build a clear future vision and set strategic goals in the field of entrepreneurship.  Training programs help develop students' courage to face challenges, risks in entrepreneurship, and make bold decisions.  Training programs have a role in enhancing students' persuasion skills to be able to influence others and push them to support their entrepreneurial projects.  Training programs have a role in enhancing the vitality and activity of students, motivating them to persevere and work continuously to achieve their goals in the field of entrepreneurship.  Training programs have a role in encouraging students to continuous self-development and providing them with the necessary skills to keep pace with changes in the market and the technological field.  Field studyprocedures:  Sample: The sample was taken by 63 students of the Sports Management and Management Division.  Time Range: Extended from November 25, 2024 to May 05, 2025.  Spatial field: Students of the Institute of Sciences and Techniques of Physical and Sports Activities, Souk Ahras University.  Methodology used: The descriptive approach was used in the survey pattern.  Used tools: In our study, we relied on a questionnaire.  Findings: The following findings have been reached:  Training programs contribute effectively to enhancing entrepreneurial thinking among students, allowing them to understand the basic principles of entrepreneurship and apply them in the field of sports management and management.  Training programs provide students with the practical skills necessary to manage sports projects and leadership in this field, whether through practical training or realistic simulation.  Suggestions:  Strengthen the focus on practical training in training programs, enabling students to gain real experience and apply the principles they have learned in the actual work environment.  Developing training programs to include training on the latest technologies and tools that contribute to improving sports and administrative performance, including sports software and modern techniques in data analysis and project management
دراسة ميدانية مع طلبة شعبة الادارة والتسيير الرياضي بجامعة سوق اهراس
Keywords: برامج التكوين; روح المقاولاتية; ريادة الأعمال; طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية; الإدارة والتسيير الرياضي; المهارات الريادية; التفكير المقاولاتي; التدريب العملي; تطوير الذات; مواجهة التحديات; مهارات الإقناع والتأثير; التكنولوجيا الرياضية; تحليل البيانات; إدارة المشاريع الرياضية; Programmes de formation; esprit entrepreneurial; entrepreneuriat; étudiants de l’Institut des Sciences et Techniques des Activités Physiques et Sportives; gestion et administration sportives; compétences entrepreneuriales; pensée entrepreneuriale; formation pratique; affrontement des défis; prise de décision; compétences de persuasion et d’influence; technologies sportives; analyse de données; gestion de projets sportifs.; Training programs; entrepreneurial spirit; entrepreneurs hip; students of the Institute of Science and Techniques of Physical and Sports Activities; sports management and administration; entrepreneurial skills; entrepreneurial thinking; practical training; self-development; facing challenges; decision-making; persuasion and influence skills; sports technology; data analysis; sports Project management